Predictors of Postoperative Pancreatic Fistula (POPF) After Pancreaticoduodenectomy: Clinical Significance of the Mean Platelet Volume (MPV)/Platelet Count Ratio as a New Predictor - Lale, Azmi; Kirmizi, Ilter; Hark, Betul Dagoglu; Karahan, Veysel; Kurt, Remzi; Arikan, Turkmen Bahadir; Aygen, Erhan (Elsevier Science Inc, 2022)
Purpose In this study, it was aimed to determine the predictors of clinically relevant postoperative pancreatic fistula (CR-POPF) following pancreaticoduodenectomy (PD) and clinical significance of mean platelet volume (MPV)/total platelet count ratio (MPR) as a new predictor for CR-POPF. Methods A total of 105 patients who underwent PD consecutively due to periampullary located diseases were included in the study. Patients were divided into two groups as CR-POPF and no postoperative pancreatic fistula (No-POPF). Demographic parameters, preoperative serum-based inflammatory indicators, surgical procedures, intraoperative findings, and histopathological parameters were recorded retrospectively from prospectively recorded patient files and compared between the groups. Results CR-POPF occurred in 16 (15.2%) patients: 8 (7.6%) were grade B and 8 (7.6%) were grade C according to the ISGPF classification. In univariate analysis, intraoperative blood loss > 580 mL (OR: 5.25, p = 0.001), intraoperative blood transfusion (OR: 5.96, p = 0.002), intraoperative vasoconstrictor medication (OR: 4.17, p = 0.014), benign histopathology (OR: 3.51, p = 0.036), and poor differentiation in malignant tumors (OR: 4.07, p = 0.044) were significantly higher in the CR-POPF group, but not significant in multivariate analysis. Soft pancreatic consistency (OR: 6.08, p = 0.013), pancreatic duct diameter < 2.5 mm (OR: 17.15, p < 0.001), and MPR < 28.9 (OR: 13.91, p < 0.001) were the independent predictors of CR-POPF according to multivariate analysis. Neoadjuvant treatment history and simultaneous vascular resection were less likely to cause CR-POPF development; however, they were insignificant. Conclusion Soft pancreatic consistency, pancreatic duct diameter, and preoperative MPR were the independent predictors of CR-POPF following PD. Decreased MPR is a strong predictor for CR-POPF and should be considered when deciding treatment strategies.
Keywords: Pancreaticoduodenectomy; Fistula; Mean platelet volume; Soft pancreas; Pancreatic duct diameter